Transforming Human Resource Planning: Building a Strong Foundation for Achieving Good Governance - Paroli, P. (Manunggal Halim Jaya, 2025)
This study aims to examine the role of digital technology-based Human Resource (HR) planning transformation in fostering good governance within the Indonesian public sector. The research methods employed include interviews with HR officials, policymakers, and information technology experts, as well as an analysis of HR planning documents from government agencies that have adopted digital technology. The findings indicate that technologies such as HR Management Information Systems (SIM-SDM), big data, and artificial intelligence (AI) have significantly improved transparency, accountability, and efficiency in HR planning. However, the main challenges identified are resistance to change, limited digital skills, and an unprepared organizational culture. Additionally, the study reveals that although technology enhances transparency in HR management, employee participation in decision-making regarding HR policies remains limited. To address these issues, the research recommends enhancing digital literacy, increasing employee involvement in HR policy planning, and conducting regular evaluations and adjustments of the implemented technologies. This study makes an important contribution to understanding the application of digital technology in HR planning, offering valuable insights for creating a more transparent, accountable, and inclusive government in the Indonesian public sector.